TANGGUNG GUGAT PENGEMBANG APARTEMEN YANG MENJUAL APARTEMEN YANG MASIH BELUM MENDAPATKAN IZIN MENDIRIKAN BANGUNAN - Tutiek Retnowati; Sandra Novialita (Fakultas Hukum Universitas Narotama, 2019)
Research entitled Liability for Apartments Developers Who Sell Apartments Who Still Have Not Got Building Permits, by addressing the issue How legal protection of consumers who buy an apartment does not have a building permit and How is the liability of apartment developers who sell apartments that still have not obtained a building permit. Research with the approach method of legislation and concept approach, obtained a conclusion as follows: Legal protection of consumers who buy an apartment does not have a building permit, that developers in building an apartment must meet the requirements of which must have IMB. Developers build apartments up to level 25, whereas they do not have an IMB (still in the process of applying for permits), have marketed their apartment, when the DKI Government prohibits apartment developers from building up to elevation / level 20. So it hurts buyers who have bought apartments at that level. Consumers and developers have been bound in the sale and purchase agreement, so that failure gives the right to the consumer to sue for damages. The liability of apartment developers who sell apartments that still do not get a building permit, that developers who failed to build, due to a ban from the DKI Government Agency, can be said to have committed unlawful acts. X Developers who commit unlawful acts, grant the consumer the right as a form of legal protection to obtain compensation